DEVELOPING ENGLISH READING MATERIALS FOR MADRASAH ALIYAH STUDENTS - Karman Karman (Langkawi: Journal of The Association for Arabic and English, 2017)
The final objective of this research is to develop English reading materials which are suitable for Madrasah Aliyah students. This research is a Research and Development (R & D) type. The subjects were students of Madrasah Aliyah Negeri Yogyakarta II, an expert, and English education students as well as English teachers. There was one instrument applied to obtain the research data, i.e. questionnaires which were distributed to different subjects of this research (in need analysis and evaluation phase). Data from the questionnaires was analyzed quantitatively. This research was conducted by following Borg and Gall’s research design (2003) in combination with Jolly and Bollitho's model design (1998) with several modifications. Based on the result of the need analysis, all students needed English reading materials which were based on their background study. Each unit of the developed English reading materials consists of 15 tasks and focus on vocabulary building, text type, and grammar. After being tried-out and evaluated, the materials were approved to fulfill the criteria of good materials. The quantitative analysis' result of the evaluation questionnaire shows that the highest mean is 3.47 and the lowest one is 2.89. Based on categorization using an ideal mean (Mi) and an ideal standard deviation (SDi), 21 of 30 statements about the materials belong to "good" category and nine statements belong to "very good" category. Thus, it can be concluded that the developed English reading materials for students of Madrasah Aliyah are already suitable and appropriate with Madrasah Aliyah students.